Scepticism and 'atitude' : a Wittgensteinian approach - Arslan, Nesibe Sena. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This study offers an examination of a certain kind of philosophical scepticism, e.g., scepticism about other minds, in relation to our way of knowing and understanding others. We take scepticism about other minds as an expression of a certain form of sceptical attitude and find its characteristics in the dualistic treatment of the mind/inner from the body/outer. Thus, we consider solipsism (as traditionally conceived) and the problem of other minds (as an extension of solipsism) with the aim to trace various conceptions of the self, particularly Descartes’ Cartesian ego. Against the backdrop of this conception, we introduce Ludwig Wittgenstein’s remark on “an attitude toward a soul” as a rejection of the Cartesian dualist framework. We then consider David Chalmers’ resurfacing of the notion of the ‘inner’ in his treatment of the problem of consciousness. We thereby argue that such a treatment assumes an explanatory gap between our notion of consciousness and the world, and thus, is a kind of reiteration of the Cartesian position that relates to Cartesian-type scepticism. Lastly, we consider a descriptive case —a sci-fi movie— in which we may find a host of ambiguities about what it means to be human as opposed to a machine. We offer our own treatment inspired by Wittgenstein’s “an attitude toward a soul” as a particular case of applying a rule or understanding a word. In so doing, we find that there is a kind of sceptical position that survives the Cartesian way of putting it.
Keywords: Wittgenstein, Ludwig, 1889-1951.; Skepticism.